Financial Constraints and Bankruptcy Risks of Listed Firms in Vietnam: Does Firm Size Matter? - Hoa Thanh Phan Le; Tuan Nhat Pham; Trang Ngoc Doan Tran; Han Gia Dang; Khoa Dang Duong (SAGE Open)
This study examines how financial constraints and total assets affect the corporate bankruptcy risk of listed firms in Vietnam. Specifically, we test whether larger firms are less financially constrained and have lower distress risk subsequently. This study employs the dynamic system Generalized Method of Moments to analyze an unbalanced sample of 1,990 firm-year observations from 2010 to 2019. The results indicate that larger firm size increases the Z-score index, implying that larger firms have lower bankruptcy risk. Our finding also reports that financial constraints reduce the Z-score index, suggesting that financially constrained firms have extremely high bankruptcy risk. Our findings also show the inverted U-shape relationship between financial constraints and distress risk. Our results support the too-big-to-fall theory, the trade-off theory, the agency theory, and prior literature. Finally, our study contributes practical implications for managing bankruptcy risks in emerging markets. JEL Classification: G30, G31.